Dawnlands : a novel - Gregory, Philippa (Gregory, Philippa. Fairmile series., 2022)
"The Fairmile series continues as the fiercely independent Alinor and her family find themselves entangled in palace intrigue, political upheaval, and life-changing secrets in 17th-century England"--